Biochanin-A: A Potential Candidate for the Treatment of Alzheimer’s Disease - Singh, Niraj Kumar; Bhushan, Bharat (Current Pharmaceutical Biotechnology, 2025)
Alzheimer's disease (AD), the most common form of dementia, is a multifactorial neurological condition characterized by progressive loss of memory and learning, uncontrollable movement, difficulty processing visual images, and impairment of reasoning and/or judgment skills. Although the exact cause of AD is still unknown, recent evidence suggests that environmental, lifestyle, and genetic factors are common contributors to the disease's progression. Pathophysiological features of AD include amyloid beta (Aβ) accumulation, abnormal deposition of neuritic plaques and neurofibrile tangles, cholinergic dysfunction, neuroinflammation, and oxidative stress burden along with mitochondrial dysfunction. There are currently no pharmaceutical methods or medications that can stop the progression of a disease. More attention is now being paid to natural products, herbal medicines, and different bioactive phytoconstituents, particularly flavonoids, as alternative therapies and useful resources for finding new drug candidates for the treatment of AD-like symptoms. A dietary isoflavone, biochanin-A, which is isolated from the leaves and stems of Trifolium pretense L. (family: Leguminosae), possesses remarkable anti-inflammatory and antioxidant properties along with cognitive-enhancing effects. Biochanin-A exhibits notable neuroprotective effects by reducing Aβ deposition, decreasing apoptosis, and preventing the production of pro-inflammatory mediators, including TNF-α, IL-1β, and NO. Various preclinical reports explore the pharmacological role of biochanin-A against experimentally-induced AD and highlight that it can alter numerous signaling pathways, including Nrf2, NF-κB, JNK, MAPK, and Bcl-2/Bax. The present review article summarizes the numerous research studies that have evaluated the role of biochanin-A for dementia associated with AD. As part of a comprehensive program, biochanin-A has very exceptional potential to prevent and treat AD-related cognitive impairment. It is envisaged that these potential chemical moieties can be employed in the drug discovery process to identify efficacious and safe therapy for the treatments for AD-like manifestation.
Keywords: neuroinflammation